Agonies of empire American power from Clinton to Biden - Cox, Michael 1947- (Bristol University Press, 2022)
Michael Cox outlines the ways in which five American Presidents from Clinton to Biden have addressed their predecessors' legacies while dealing with an empire under increasing stress. He sets out a critical framework for US foreign policy, the US's relationship with its enemies and rivals, and whether it is now in long term decline